Toric Geometry and Calabi–Yau Compactifications - Kreuzer, M. (Український фізичний журнал, 2010)
These notes contain a brief introduction to the construction of toric Calabi–Yau hypersurfaces and complete intersections with a focus on issues relevant for string duality calculations. The last two sections can be read independently and report on recent results and work in progress, including torsion in cohomology, classification issues, and topological transitions. Цi нотатки мiстять короткий вступ до побудови торiчних Калабi–Яу гiперповерхней та повних перетинiв з акцентом на розрахунках, що стосуються дуальностi струн. Останнi два роздiли можуть бути прочитанi незалежно вiд iнших i присвяченi недавнiм результатам та роботам, якi ще не закiнчено, включаючи кручення в когомологiї, питання класифiкацiї та топологiчних переходiв.